Contrasted Types of Metamorphism of Basic Intrusiions in the Precambrian Basement of the Tasîussaq Area, South Greenland. - Dawes, Peter R. (Meddelelser om Grønland, 1968)
Metamorphosed rocks of three distinct episodes of basic intrusion can be recognised in the Precambrian basement of the Tasiussaq area, South Greenland. The oldest intrusions, represented by sills and dykes, are pyriclasites and biotitepyriclasites; the second episode intrusions , in the form of dykes, are pyroxenemetadolerites and the third episode intrusions, represented by dykes and small bodies, are metagabbros, metadolerites, metanorites and amphibolites. The metamorphic nature of the rocks of the three episodes is a reflection of age. Chemical and modal analyses of rocks from the three episodes are presented. Fresh diorite sills and dolerite dykes represent later episodes of Precambrian basic intrusion . The basic rocks depict the varying types of metamorphic conditions which affected the area in Precambrian time and these are seen to differ from the established metamorphic history in areas to the north-west in South Greenland. The pyriclasites and biotite-pyriclasites have been derived through granulite facies metamorphism; the pyroxene-metadolerites by dipsenic metamorphism under conditions corresponding to the amphibolite facies and the metagabbros, metadolerites, metanorites and amphibolites through amphibolitisation during amphibolite faci es metamorphism. It is suggested that the metamorphism producing the pyroxene-metadol erites (Sanerutian in age) was controlled by dipsenic conditions inherited from earlier granulite facies metamorphism (Ketilidian in age). This implies that the Ketilidian and Sanerutian metamorphisms in the Tasiussaq area are not separated by a long span of time and that the break in plutonism marked by the pyroxene-metadolerites cannot be regarded as a significant cratogenic hiatus between two separate plutonisms. The importance of water in controlling t rends in the metamorphism of dolerites is stressed. The 1st episode intrusions have undergone severe changes since intrusion and no palimpsest features indicative of primary texture or mineralogy remain. The majority of the 2nd episode intrusions display a granular texture, but some display sub-ophitic and relic sub-ophitic textures. The 3rd episode intrusions display a range from ophitic, sub-ophitic and microporphyritic textures to relic stages of these textures. The 1st episode intrusions were emplaced into a geosynclinal pile of sediments and were probably connected with the volcanicity which occurred at the end of sedimentation. The 2nd and 3rd episode intrusions were emplaced into granitic and metamorphic rocks at a later stage in the same 'geological cycle'. Both the 2nd and 3rd episode intrusions are considered to indicate trends in the crust towards brittle conditions marking temporary partial withdrawals of the thermal front. Their preserved ophitic and sub-ophitic textures are not indicative of emplacement and crystallisation in cratogenic conditions.